Alterações fisiológicas e reprodutivas em Pseudosuccinea columella (Mollusca: gastropoda) após infecção experimental por Heterorhabditis baujardi (Rhabditida: heterorhabditidae) cepa LPP7 - Vidal, Maria Larissa Bitencourt (2020)
Mollusc Pseudosuccinea columella participates in the prevalence of fasciolosis, leading to a distribution of the disease, as well as developing forms of control. This study attested under laboratory conditions the suceptibility of P. columella to Heterorh